2006
DOI: 10.1093/intimm/dxl105
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic HLA-B7-restricted peptides of hTRT

Abstract: Telomerase reverse transcriptase (TRT) is the first bona fide common tumor antigen. While several 9mer peptides of the human TRT have been identified for HLA-A2, little information exists on peptides for the remaining HLA types. Here, we used a multi-step approach to select and characterize a panel of HLA-B7 9mer peptides as candidate immunogens. In sequence, we used algorithm-based predictions, in vivo immunization of HLA-B7 transgenic (Tg) mice, in vitro immunization of human blood lymphocytes from two norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Previous studies have explored minigene vaccines comprising multiple contiguous minimal murine CTL epitopes 47 or contiguous dominant HLA-A*0201 and HLA-A*11-restricted epitopes from the polymerase, envelope, and core proteins of hepatitis B virus and HIV, together with the PADRE (pan-DR epitope) universal T-cell epitope and an endoplasmic reticulum-translocating signal sequence 48 . However, processing of individual epitopes in these minigenes is not assured due to the non-specific nature of proteasomal processing 49 . The approach of inserting AAY spacers between the epitopes and the use of ubiquitin as a protein-targeting sequence was previously tested in the context of minigenes containing CTL epitopes derived from MPT64 and 38 kDa proteins of Mycobacterium tubercolosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored minigene vaccines comprising multiple contiguous minimal murine CTL epitopes 47 or contiguous dominant HLA-A*0201 and HLA-A*11-restricted epitopes from the polymerase, envelope, and core proteins of hepatitis B virus and HIV, together with the PADRE (pan-DR epitope) universal T-cell epitope and an endoplasmic reticulum-translocating signal sequence 48 . However, processing of individual epitopes in these minigenes is not assured due to the non-specific nature of proteasomal processing 49 . The approach of inserting AAY spacers between the epitopes and the use of ubiquitin as a protein-targeting sequence was previously tested in the context of minigenes containing CTL epitopes derived from MPT64 and 38 kDa proteins of Mycobacterium tubercolosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune response can be induced by exposure to antigen presenting cells that either overexpress immunogenic hTERT fragments [92] or have been pulsed with immunogenic hTERT peptides. To date, 26 different hTERT peptides have been utilized to elicit an anti-telomerase immune response [88,97,101,102,104111]. Vaccination studies using the I540–548 peptide have produced functional anti-tumor responses in prostate, breast and melanoma patients [89,96,112].…”
Section: Telomerase-targeted Immunotherapymentioning
confidence: 99%
“…Thus, p540 might be expressed at only the low end of natural antigen-presentation levels (~10 copies per cell) 22,23 . Over the years, further evidence showed that TERT is processed endogenously, and that TERT peptides are presented by cancer cells that express HLA-A*03, HLA-A*24, and HLA-B*7 MHC I molecules [24][25][26][27][28] .…”
Section: Tert Immunology In Cancermentioning
confidence: 99%
“…This finding is important because immunization does not result in the de novo creation of antigenspecific T cells, but rather the selective expansion of reactive clones that pre-exist in the T-cell repertoire 15,16,24,26,28,33 . The in vivo immunogenicity of TERT has also been interrogated in preclinical models using a variety of approaches, including synthetic TERT peptides 15,24,28 , dendritic cells (DCs) transfected with TERT mRNA [34][35][36] , and DCs transduced with TERT-adenovirus 37 , TERT-encoding lentivirus vectors 38 , and plasmid DNA encoding TERT 39 . In selected instances, the induction of T-cell responses was associated with inhibition of tumour growth 34,[38][39][40][41] .…”
Section: Autoimmunity and Tert Vaccinesmentioning
confidence: 99%